2020
DOI: 10.26487/hjabe.v3i2.316
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Motivation and Job Satisfaction on Employee Performance in Pt. Son Karella Mare

Abstract: Every company wants high-performing human resources. This study aims to determine the effect of motivation and job satisfaction on employee performance at PT. Putra Karella Mare directly and mediation. This study uses a quantitative approach that aims to explain the position of the variables studied as well as the relationship between one variable with another with the intention to test hypotheses that have been formulated previously. This study will explain the causal relationship between variables through hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
8
1
2
Order By: Relevance
“…[19-21, 1, 22, 18, 23-26] find that motivation has a significant effect on employee performance. But different from the results of research [27][28][29][30]12] which found that motivation had no significant effect on employee performance.…”
Section: Effect Of Motivation On Employee Performancecontrasting
confidence: 78%
See 2 more Smart Citations
“…[19-21, 1, 22, 18, 23-26] find that motivation has a significant effect on employee performance. But different from the results of research [27][28][29][30]12] which found that motivation had no significant effect on employee performance.…”
Section: Effect Of Motivation On Employee Performancecontrasting
confidence: 78%
“…Motivation aims to change the motivation in employees to be higher [4,11] says motivation can increase energy which will have an impact on improving performance. So job satisfaction in achieving organizational goals will be affected, and lead to higher job satisfaction [4,10,12] found that motivation had a significant effect on job satisfaction.…”
Section: Effect Of Motivation On Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study explain that the role of job satisfaction in mediating motivation and the performance of MSC Clinic employees is acceptable. Some research results suggest that motivation can increase energy, which will have an impact on job satisfaction and lead to higher employee performance (Pananrangi et al, 2020 (Efendi & Yusuf, 2021), which states that competence has a positive and significant effect on employee performance through job satisfaction as an intervening factor.…”
Section: The Effect Of Motivation On Employee Performance Is Mediated...mentioning
confidence: 99%
“…Meanwhile, employee performance denotes an individual's ability to perform and complete a task to help the organization achieve its goals. For this reason, it is imperative to conduct an objective performance assessment to assist the leader in improving the employee's performance (Pananrangi et al, 2020).…”
Section: Employee Performancementioning
confidence: 99%